2023
DOI: 10.5194/acp-23-8103-2023
|View full text |Cite
|
Sign up to set email alerts
|

Levels of persistent organic pollutants (POPs) in the Antarctic atmosphere over time (1980 to 2021) and estimation of their atmospheric half-lives

Abstract: Abstract. Persistent organic pollutants (POPs) are synthetic compounds that were intentionally produced in large quantities and have been distributed in the global environment, originating a threat due to their persistence, bioaccumulative potential, and toxicity. POPs reach the Antarctic continent through long-range atmospheric transport (LRAT). In these areas, low temperatures play a significant role in the environmental fate of POPs, retaining them for a long time due to cold trapping by diffusion and wet d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 112 publications
(165 reference statements)
0
1
0
Order By: Relevance
“…These antibiotics exhibit ionic properties in the elevated pH, which is indirectly induced by the eutrophication in the Pearl River. Organic species originating from the ocean can enter the atmosphere via two principal mechanisms: the generation of sea spray aerosols through bubble bursting and wind shear, along with the release of volatile organic compounds from the ocean surface. Studies have illustrated that phytoplankton biomass significantly influences aerosol particles generation through wave breaking in both sea and lake environments, leading to an enrichment of matter at the air–water interface. The aerosolization of phytoplankton cells and fragments occurs across a size spectrum ranging from fine (<2.5 μm) to coarse (2.5–10 μm), with microalgal abundance in the atmosphere varying from 10 –4 to 10 4 cells m –3 . , This work revealed that antibiotics transfer to the atmosphere primarily through aerosolization, controlled by phytoplankton biomass. By linearly plotting the concentrations in aerosol-phase concentrations of antibiotics C air against the biomass, negative correlations between C air and phytoplankton biomass were observed in general (Figures a).…”
Section: Resultsmentioning
confidence: 99%
“…These antibiotics exhibit ionic properties in the elevated pH, which is indirectly induced by the eutrophication in the Pearl River. Organic species originating from the ocean can enter the atmosphere via two principal mechanisms: the generation of sea spray aerosols through bubble bursting and wind shear, along with the release of volatile organic compounds from the ocean surface. Studies have illustrated that phytoplankton biomass significantly influences aerosol particles generation through wave breaking in both sea and lake environments, leading to an enrichment of matter at the air–water interface. The aerosolization of phytoplankton cells and fragments occurs across a size spectrum ranging from fine (<2.5 μm) to coarse (2.5–10 μm), with microalgal abundance in the atmosphere varying from 10 –4 to 10 4 cells m –3 . , This work revealed that antibiotics transfer to the atmosphere primarily through aerosolization, controlled by phytoplankton biomass. By linearly plotting the concentrations in aerosol-phase concentrations of antibiotics C air against the biomass, negative correlations between C air and phytoplankton biomass were observed in general (Figures a).…”
Section: Resultsmentioning
confidence: 99%